Asymptotics semiclassically concentrated on curves for the nonlocal Fisher-Kolmogorov-Petrovskii-Piskunov equation; Journal of Physics A: Mathematical and Theoretical; Vol. 49, № 30 - Levchenko E. A. Evgeny Anatolievich (2016, 2016)
Title screen